Characterization of SAR Clutter and Its Applications to Land and Ocean Observations - Gao, Gui (Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses statistical modeling of single- and multi-channel synthetic aperture radar (SAR) images and the applications of these newly developed models in land and ocean monitoring, such as target detection and terrain classification. It is a valuable reference for researchers and engineers interested in information processing of remote sensing, radar signal processing, and image interpretation.